Peran “Teologi Sosial” Gereja Protestan Indonesia Di Gorontalo (GPIG) Dalam Menanggapi Masalah Kemiskinan - Rudy Harold (Jurnal Jaffray, 2017)
Artikel ini bertujuan untuk melihat peran “teologi sosial” yang berkembang di lingkungan Gereja Protestan Indonesia di Gorontalo (GPIG) dalam menanggapi masalah kemiskinan dan ketidakadilan sosial. Berdasarkan hasil penelitian, teologi sosial yang dikembangkan di GPIG dalam menanggapi masalah kemiskinan bersumber dari refleksi teologi GPIG tentang gereja (eklesiologi) dan keselamatan (soteriologi). Hal ini berdasarkan kajian terhadap dokumen – dokumen Tata Gereja GPIG tentang Pokok Panggilan dan Tugas GPIG serta pemahaman tentang keselamatan yang terkandung dalam Tata Gereja GPIG.This article aims to examine the social theology that is alive and thriving in the Indonesian Protestant Church in Gorontalo (GPIG) in response to the problem of poverty and social injustice. The data analyzed comes from theological thinking articulated by individuals (pastors, teachers of religion, elders, deacons) as well as theological thinking and attitudes of the GPIG as a religious institution, as reflected in the results of the trial of the congregational level to the sinodal level. Based on the research results, the social theology developed in the GPIG in response to problems of poverty, is sourced from GPIG theological reflection on the church (ecclesiology) and salvation (soteriology). It is based on a review of the Basic Rules of GPIG documents about the Principal Calling and Duties of the GPIG as well as an understanding of salvation contained in the Basic Rules of GPIG.